Risk assessment for an acetone storage tank in a chemical plant in Istanbul, Turkey: Simulation of dangerous scenarios. Issue 4 (8th April 2021) - Iskender, Hikmet
Abstract: Acetone is one of the most commonly used materials in industry, mainly as a strong solvent in drug, plastic, fiber, paint, and other industries. Acetone is a colorless liquid which evaporates easily and is also a hazardous chemical with consequences of exposure ranging from injuries to death. The release of acetone from a storage tank is a potential hazard to workers, plants, and also the environment. To decrease the impact of acetone vapor, puddle, and leakage, industrial plants have a mitigation plan based on risk reduction for acetone. The aim of this paper is to obtain risk distribution for accidental acetone release from a storage tank by modeling with Areal Location of Hazardous Atmosphere software. Risk distribution was defined in three threat zones. The red threat zone, orange threat zone, and yellow threat zone were determined to extend to distances of 62, 85, and 400 m for the toxic area of acetone vapor cloud; the red threat zone and yellow threat zone were calculated to be 35 and 95 m for the flammable area; and the orange threat zone and yellow threat zone were found to be 27 and 46 m for vapor cloud explosion. Moreover, the maximum average evaporation rate of acetone was 176 g/min. This paper demonstrates important modeling to prevent acetone‐related accident risks in an industrial plant.